Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-67 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Practical judgment of extensor spasticity. When the Author holds the patient Nefeli (SCI Th10), one can judge her extensor spasticity by the extension of her legs (A). Her present spasticity is medium strong. A physiologic leg position can be seen in B. The healthy seven-year-old sister has no spasticity and the legs are flexed.